2021
DOI: 10.3389/fpubh.2021.656036
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Symptoms, Binge Drinking, and the Experience of Abuse During the COVID-19 Lockdown in Mexico

Abstract: Background: The health crisis associated with the COVID-19 pandemic is causally linked to negative mental health symptoms in the same way as other diseases such as Ebola.Objective: The purpose of this paper is to describe the relationship between mental health symptoms, binge drinking, and the experience of abuse during the COVID-19 lockdown.Method: We surveyed 9,361 participants, all Mexican, with an average age of 33 years old (SD = 10.86). In this group of people, we found out that 59% were single (5,523), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…There were 10 articles excluded due to their study methodology, not being related to the main objective, not having enough data or because they were reviews. After a meticulous review of each article, 15 studies met the inclusion criteria [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 10 articles excluded due to their study methodology, not being related to the main objective, not having enough data or because they were reviews. After a meticulous review of each article, 15 studies met the inclusion criteria [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety symptoms were analyzed in 11 out of the 15 studies [ 13 , 14 , 15 , 16 , 17 , 19 , 22 , 23 , 25 , 26 , 27 ], with a variation in the prevalence of anxiety symptoms from 11.9% to 93.7%. In Pérez-Cano et al [ 13 ], 48.8% of individuals had anxiety from mild to very severe associated with the COVID-19 pandemic; moreover, 18.6% of these also experienced other symptoms such as stress from moderate to very severe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported 37.54% suffering from stress, 38.12% from anxiety, and 34.31% from depression and pointed out COVID-19 as a potential public mental health problem for the global community. In Mexico, Morales-Chainé et al (2020, 2021a reported high frequencies of stress, sadness, and anxiety symptoms according to an evaluation of 33,044 participants during the COVID-19 pandemic. These studies reported that mental health symptoms have varied due to sex, COVID-19 condition, alcohol abuse, and suffering from abuse.…”
Section: Introductionmentioning
confidence: 99%